“If a Person Must Die, Then So Be It”: A Constitutional Perspective on South Africa’s Land Crisis - Dylan Hitchcock-Lopez (Washington University Journal of Law & Policy, 2019)
This note addresses the ongoing process of land reform in South Africa. It particularly focuses on one of the three land reform pillars laid out in South Africa’s constitution—security of tenure. The note argues that, in light of the Constitutional Court’s holding that communities may possess collective rights of land ownership, legislation should be enacted to vindicate these rights. Rather than attempting to articulate exhaustively the substance of communal land rights, the proposal emphasizes procedural rights, effective dispute resolution, and affordable modern surveying methods as a way of efficiently providing a trajectory toward tenure security within the capacity of official resources.
Keywords: South Africa; constitutional; land reform; security of tenure; procedural rights; effective dispute resolution; communal land rights; racial discrimination